The Marginal Productivity Theory of Wages and Disguised Unemployment - Mazumdar, Dipak (Review of Economic Studies, 1959)
The Marginal Productivity Theory of Wages and Disguised Unemployment Get access Dipak Mazumdar Dipak Mazumdar London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 3, June 1959, Pages 190–197, https://doi.org/10.2307/2295747 Published: 01 June 1959